Crystal Structure and Luminescent Properties of Supramolecular Compound [C12H12N2]2+[C16H8O10S]2- - Tang, Long; Wu, Ya-Pan; Fu, Feng; Hou, Xiang-Yang; Wang, Ji-Jiang (Asian Journal of Chemistry, 2012)
A new supramolecular compound [C12H12N2]2+[C16H8O10S]2- was synthesized and characterized by elemental analysis, IR and single-crystal X-ray diffraction. In the crystal structure, multiform hydrogen bonds (N-H···O and C-H···O) lead to a three-dimensional supramolecular architecture. The luminescent properties of the compound in the solid state were investigated. The crystal be longs to monoclinic, space group C2/c, a = 3.039(3), b = 0.48803(7), c = 2.0251(2) nm, b = 100.319(2)º, Z = 4, V = 2.955(3) nm3, R1 = 0.0664 and wR2 = 0.1637 (CCDC 754951).